The Efficacy and Safety of Infliximab in Refractory Noninfectious Uveitis: A Meta-Analysis of Observational Studies - Xiong, Anji; Liu, Deng; Chen, Huini; Yang, Guancui; Xiong, Chen; Shuai, Yu; He, Linqian; Guo, Zepeng; Zhang, Liangwen; Yang, Yuan; Cui, Beibei; Shuai, Shiquan (Frontiers in Pharmacology, 2021)
Background: Although Infliximab has been recommended for the second-line treatment of seronegative spondyloarthropathy- or juvenile idiopathic arthritis-related uveitis, the issue of its systemic efficacy and safety in broader diversity of refractory non-infectious uveitis is debatable. To assess the short-term and relatively long-term efficacy of Infliximab in refractory non-infectious uveitis, we performed a systematic review and meta-analysis of observational studies. Methods: PubMed, Cochrane libraries, Embase and Wanfang Med Online were systematically searched from January 2005 to March 2020. Two investigators independently assessed eligibility. Data were independently collected by two investigators. The pooled proportions were estimated with patients for intraocular inflammation control and improvement of visual acuity. Pooled proportions with 95% credible intervals were computed. Study homogeneity was investigated using I² statistic to quantify the percentage of variation across studies. To pool the results, the Mantel–Haenszel fixed-effects or random-effects models were used. Results: Of 2316 studies identified, 16 unique studies with 509 unique participants were included in the meta-analysis. The pooled proportions of intraocular inflammation control reached 92% (95% CI 87%-98%; I²:1%; p=0.42) and 95% (95% CI 93%-97%; I²:0%; p=0.91) in groups of ≤6- and ≥12-months follow-up durations. During the relatively long follow-up period, the pooled proportions of maintaining visual acuity stable or increasing at least one line reached 99% (95% CI 96%-100%; I²:0%; p=0.54) in the involved eyes. Corticosteroid-sparing effect of infliximab was also well demonstrated, with the proportion of corticosteroid-sparing success reaching 85.5% (112/131). Besides, about serious adverse effects, 1.8% (9/500) patients experienced autoimmune diseases, 0.6% (3/500) patients experienced neoplasia, 2.6% (13/500) patients experienced hypersensitivity reactions and 2.4% (12/500) patients experienced serious infections. Conclusions: This meta-analysis provided evidences that Infliximab might be a promising choice in controlling inflammatory activity, gaining visual acuity, and sparing corticosteroid use with relatively few side effects when applied in treating refractory non-infectious uveitis.